Rationalization of a nanoparticle-based nicotine nanovaccine as an effective next-generation nicotine vaccine: a focus on hapten localization - Zhao, Zongmin (Biomaterials, 2017)
A lipid-polymeric hybrid nanoparticle-based next-generation nicotine nanovaccine was rationalized in this study to combat nicotine addiction. A series of nanovaccines, which had nicotine-haptens localized on carrier protein (LPKN), nanoparticle surface (LPNK), or both (LPNKN), were designed to study the impact of hapten localization on their immunological efficacy. All three nanovaccines were efficiently taken up and processed by dendritic cells. LPNKN induced a significantly higher immunogenicity against nicotine and a significantly lower anti-carrier protein antibody level compared to LPKN and LPNK. Meanwhile, it was found that the anti-nicotine antibodies elicited by LPKN and LPNKN bind nicotine stronger than those elicited by LPKN, and LPNK and LPNKN resulted in a more balanced Th1-Th2 immunity than LPKN. Moreover, LPNKN exhibited the best ability to block nicotine from entering the brain of mice. Collectively, the results demonstrated that the immunological efficacy of the hybrid nanoparticle-based nicotine vaccine could be enhanced by modulating hapten localization, providing a promising strategy to combatting nicotine addiction.